Cooling load reduction in office buildings of hot-arid climate, combining phase change materials and night purge ventilation. (January 2016) - Solgi, Ebrahim; Fayaz, Rima; Kari, Behrouz Mohammad
Abstract: Night purge ventilation is a well-known passive technique for conserving cooling energy by storing night coolth in the thermal mass of the building fabric. We study the effect of phase change materials (PCM) as a light thermal mass, on the cooling load of a typical office building with HVAC system and night purge ventilation in hot-arid climate. In this paper the proper conditions to start night ventilation and the ventilation rate by fans is determined. Additionally, the effect of melting point temperature of the PCMs on the cooling load of the building is investigated. PCMs with proper melting temperature were applied to various building elements, and to the whole model. It was revealed that, application of PCMs will significantly contribute in reducing the cooling load, except for the floor on the ground, which resulted in an increase of the load. Highlights: A simple office building model, using PCMs, in hot-arid climate was simulated. Conditions to start night ventilation, regarding outdoor temperature were defined. The proper PCM was selected and its effect on building elements was studied. By integrating PCMs and night purge ventilation daytime overheating hours reduced. PCM in building elements reduce the cooling load except for the floor on the ground.